Bone anabolic changes progress in psoriatic arthritis patients despite treatment with methotrexate or tumour necrosis factor inhibitors. Issue 7 (21st August 2012) - Finzel, Stephanie; Kraus, Sebastian; Schmidt, Sarah; Hueber, Axel; Rech, Juergen; Engelke, Klaus; Englbrecht, Matthias; Schett, Georg
Abstract : Objectives: To investigate whether methotrexate or tumour necrosis factor inhibitors (TNFi) affect osteophyte formation in patients with psoriatic arthritis (PsA). Methods: 41 patients with PsA were examined for the presence of osteophytes and erosions at the metacarpophalangeal joints by high-resolution micro-CT imaging. The size of each individual lesion was quantified at baseline and 1-year follow-up in PsA patients treated with TNFi (N=28) or methotrexate (N=13). Groups were comparable for age, sex, disease duration and activity and baseline burden of osteophytes. Results: In total, 415 osteophytes (TNFi N=284, methotrexate N=131) were detected. Osteophyte size increased significantly from baseline to follow-up in the TNFi group (mean±SEM change +0.23±0.02 mm; p<0.0001) and the methotrexate group (+0.27±0.03 mm, p<0.0001). In both treatment groups, the majority of osteophytes showed progression (TNFi 54.3%, methotrexate 61.1%), whereas regression of lesions was rare (less than 10%). In contrast to osteophytes, clinical disease activity decreased in both groups of PsA patients and erosions showed an arrest of progression in both groups. Conclusions: Osteophytes progress in PsA patients treated with either methotrexate or TNFi. These data provide the first evidence that pathological bone formation in the appendicular skeleton of patients with PsA is not affected by current antirheumatic treatment strategies.